THE LEVEL OF AWARENESS OF EDUCATORS AND TEACHERS OF A SPECIALIZED ORPHANAGE IN THE ISSUES OF DEVELOPING SELF-CARE SKILLS TO CHILDREN WITH SEVERE MENTAL RETARDATION (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents the results of a study of the level of awareness of educators and teachersof a specialized orphanage about the development of self-care skills in various fields of activity ofchildren with severe mental retardation.The surveys, interviews and questionnaires have shown that the overwhelming majority(87.2%) of the interviewed specialists consider it important to form and develop the skills andabilities of self-care in children with severe mental retardation in a specialized orphanage. On theother hand, only 52.3% of interviewees believe that they have a sufficient level of awareness in theissues studied, 69.2% of the surveyed educators and teachers are not familiar in practice with thespecial methodological literature and the work experience of leading specialists about thedevelopment of self-care in this group of children. Therefore, in the practice of educating the skillsand abilities of self-care skills in various fields of activity while working with children, theinterviewed educators and special teachers rely on personal experience and knowledge, but not onmodern methodological developments and the advanced experience of leading specialists.The results of this research made it possible to determine the main directions oforganizational works for expanding the level and awareness, the acquisition of theoreticalknowledge and practical skills and abilities by educators and teachers of a specialized orphanage148aimed at the formation and development of self-care skills of children with a severe mentalretardation.
Keywords: children with a severe degree of mental retardation, self- service, educators, teachers, level of development, specialized Orphanage